A Method for Multihole Blasting Seismic Wave Prediction and Its Application in Pillar Recovery - Xie, Lianku; Xiong, Daiyu; Yang, Tianhong; He, Li; Yu, Qinglei (Frontiers in Physics, 2021)
Longhole blasting in mines is likely to cause strong vibration of surficial infrastructure, greatly damage the rock mass surrounding goaf near explosion centre, and possibly induce blast vibration disasters. In this paper, an improved method for multi-hole blasting seismic wave prediction based on the single-deck blast vibration fundamental wave is proposed to estimate blast vibration effect. The vibration fundamental wave is firstly obtained through a serial of blast vibration tests of single-deck signature longhole blast. Then the vibration fundamental wave is used to simulate the vibration waveform from single-deck holes in production blast with consideration of practical blasting conditions. The vibration waveform from single-deck holes is used to predict the possible vibration waveform of production blast with multiple longholes by linear superposition method according to different delay time intervals. By analysing the components of this predicted waveform of production blast, the blasting effects are estimated and sequently the blast design will be optimized to determine the rational delay time. The proposed method was applied in pillar recovery of Hongling Polymetallic Mine to optimize the longhole blast design to control the blast vibration effect. Using the proposed method, the rational delay time interval of the blast design for the 716 production site is recommended as 26 ms and the maximum single-deck permitted charge weight were determined to match the pillar recovery plan. The practice showed that the peak particle velocity of blast vibration induced by the 716 production blast stay within the safety standard range, and the predicted and the measured waveforms agree well. It effectively solved the contradiction between overall blasting of ore pillars and blast vibration control, and eliminated the harmful effect to the subsurface and surface structures.